Performance Evaluation of Financial Management by the City Government of Tegal, Indonesia During the COVID-19 Pandemic Period - Pulung Adiluhung Putro; Vicky Oktavia; Ana Kadarningsih; Linda Ayu Oktoriza (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to analyze the effectiveness of public sector financial management using five financial ratios and measure changes in Tegal City's Regional Budget (APBD) from 2020 to 2023. The research method uses a quantitative descriptive approach with secondary data from Tegal City's Budget Realization Reports. The results show the best Effectiveness Ratio occurred in 2021-2023 (81-90%), the highest Independence Ratio was in 2020 (77%), the most optimal Efficiency Ratio was in 2020 (7%), the best Degree of Decentralization Ratio was in 2022-2023 (31%), and the highest PAD Growth Ratio was in 2021-2023 (83-105%). Overall, Tegal City's financial performance from 2020-2023 showed positive trends in effectiveness and PAD growth, but requires improvements in efficiency and fiscal independence. The study provides recommendations for the Tegal City Government to optimize regional financial management through improved budget efficiency and reduced dependence on central government funds.